ANALISIS DETERMINAN KEMISKINAN DI JAWA TIMUR TAHUN 2018 - Ris Yuwono Yudo Nugroho; Sofia Janahtul Isnaini Janahtul Isnaini (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2020)
Poverty is a multidimensional concept that includes dimensions as lack of opportunity, lack of empowerment, and lack of security. This study aims to analyze the determinants of poverty and their effects on poverty in East Java Province. This research uses quantitative methods, and the data used are data from the Central Statistics Agency of East Java Province. The type of data used is a cross-section in 2018. This study uses multiple linear analysis (OLS) with poverty as the dependent variable, economic growth (GRDP), labor force, and APBD as independent variables. It uses regional dummy variables to see the effect of poverty enclaves on poverty in East Java. Dummy 1 for the “tapal kuda” area, and dummy 2 for the Madura island area. The results showed that the GRDP and regional budget had a negative and significant effect on poverty. Labor force variables have a positive and significant impact on poverty in East Java Province in 2018. Dummy 1 (D1) has a probability of 0.6532 (> 0.05), which means that the D1 variable is not significant to poverty in East Java. Then for the D2 variable or region on the island of Madura has a probability level of 0.0233 (<0.05), which means significant for poverty in East Java in 2018